Effect of 4-biphenyl groups on the charge transport and photovoltaic properties of arylamine based push–pull systems. (21st May 2020) - Marqués, Pablo Simón; Andrés Castán, José María; Josse, Pierre; Blais, Martin; Habibi, Amir Hossein; Ramirez, Ivan; Walzer, Karsten; Roncali, Jean; Blanchard, Philippe; Cabanetos, Clément
Abstract : The synthesis of two N, N -bis(4-biphenylyl)aniline (BPA) based push–pull is reported herein. Evaluation as donor materials in all-small-molecule planar-heterojunction organic solar cells lead to impressive fill factor (>73%) and promising power conversion efficiencies. Abstract : Two push–pull derivatives based on a N, N -bis(4-biphenylyl)aniline (BPA) donor block connected to a dicyanovinyl accepting moiety by thienyl and bithienyl π-conjugated spacers have been synthesized and characterized. All-small-molecule planar-heterojunction organic solar cells show promising power conversion efficiencies and impressive fill factor (>73%) correlated with the high hole-mobility induced by the BPA moiety.